MICRO TEACHING PRACTICE IN INTRODUCING TEACHING METHODS AND TECHNIQUES FOR STBA PONTIANAK STUDENTS - Julhijah, Novita (IKIP PGRI Pontianak, 2017)
Language is the key of communication. Teacher needs some efforts in teaching especially in applying the teaching techniques in the classroom in order to meet the objective of the study. This descriptive â qualitative research told about the effectiveness of micro teaching in applying some techniques and obstacles in having the micro teaching. Since some of the students did not have some backgrounds of teaching so, they needed teaching practices to apply some techniques effectively (collaboration, student-student interaction, grouping) the practices can help them implement some teaching techniques which can be used in the final project (in the real life classroom). The research participants were 16 students of the last semester and the data collections were video recording of studentsâ activities in the classroom,Â pictures of the teaching aids and the classroom evaluation checklist. As the fisrt start, the lecturer explained completed lesson plannings and generic lesson plans and some teaching techniques and methods. The study showed a satisfying result in that Â most of the students could have good score in the final assessment.Keywords: techniques, methods, teaching practice.